Evaluating advanced automotive energy technologies: a multivariate mobility contribution metric. (13th September 2004) - Burns, Joseph; Cors, Thomas; Knight, Brian; Thelen, Brian
Mobility technology is beginning to shift from gasoline-fuelled, internal combustion engines to a variety of alternate fuels and powertrains, including hybrid and fuel cell vehicles. The benefits and/or limitations of many of these technologies are not well characterised by a simple fuel economy metric: mobility is a complex system requiring a multivariate systems measure, especially incorporating "well-to-wheel" energy use. This paper provides such a multivariate metric that is intended as a decision support tool for policy makers, as well as a method for finding a consensus set of indicators with stakeholder groups.